The Expectation about Factory Isolation of Workplaces within the Industrial Estates that Join the Project with a Government Hospital during Pandemic of COVID-19 - Kalyawuttipong, Poramat; Prasan, Shewarat; Chongchitpaisan, Wanna; Bundhukul, Adul; Thongdee, Chitrada (Journal of Preventive Medicine Association of Thailand, 2023)
Background: The COVID-19 pandemic had a significant impact on healthcare systems and the global economy, with many companies struggling to operate effectively due to infections in the workplace. To address this issue, the government implemented policies requiring factories to establish their own factory isolation programs based on hospital guidelines in order to control infections in the workplace. Objective: The study aimed to investigate the expectations of factories regarding the support provided by hospitals in setting up their own factory isolation programs based on hospital guidelines, with the goal of controlling infections in the workplace. Methods: A cross-sectional descriptive study was conducted among 140 workplaces between January 3 to March 31, 2022, to evaluate the expectations of these factory isolation programs. Descriptive statistics were used to evaluate the mean expectations for each aspect, and the mean expectation point of all factories was used to separate high and low expectation factories. Multiple logistic regression was used to determine the crude and multivariable odds ratios between various factors related to screening and diagnostic infection, treatment of COVID-19 patients, caring for high-risk contacts, and health promotion and disease prevention with workplace expectations. Results: The results of the study showed that the treatment of COVID-19 infection (81.7±16.3%) and screening and diagnostic infection factors (81.2±15.0%) had the highest expectations among all 140 factories. However, the lowest expectation aspect was health promotion and disease prevention factors (73.3±17.9%). The associated factor with workplace expectations was the treatment of COVID-19 patients, with the presence of an occupational physician consultant in the factory being 2.5 times more likely to have high expectations (95%CI: 1.0-6.3; p = 0.048). Conclusion: The study provides valuable information for COVID-19 management and other pandemics by highlighting the importance of proper and efficient factory isolation programs. By addressing areas of higher expectations, such as treatment of infection, and ensuring the presence of an occupational physician consultant in the factory, factories can better prepare for and respond to future pandemics.